Shen-Hong-Tong-Luo formula ameliorates atherosclerosis by enhancing macrophage efferocytosis through activating the PPARγ/mfge8 pathway - Shi, Yanyu; Zhang, Zepeng; Liu, Jiaqi; Xu, Xiaolin; Xiao, Xue; Zhang, Tianyang; Zhang, Yuan; Cui, Haoran; Li, Xiangyan; Chen, Ying (Frontiers in Immunology, 2026)
BackgroundAtherosclerosis (AS) is a chronic inflammatory disorder driven by dysregulated lipid metabolism and remains a leading cause of cardiovascular morbidity. The Shen−Hong−Tong−Luo (SHTL) preparation has demonstrated clinical benefit in stabilizing atherosclerotic plaques, yet its molecular mechanisms are not fully defined.PurposeThis research sought to elucidate the protective effects exerted by SHTL on AS progression.MethodsTo investigate the impact of SHTL on macrophage function and plaque stability, we utilized ApoE-/- mice models and bone marrow-derived macrophages (BMDMs) stimulated with lipopolysaccharide (LPS) and oxidized low-density lipoprotein (Ox-LDL). Network pharmacological analysis was conducted to predict potential therapeutic targets of SHTL, with a particular focus on the efferocytosis pathway. These predictions were subsequently confirmed by immunofluorescence (IF) staining and flow cytometry experiments performed on ApoE-/- mice and BMDMs. Furthermore, using data-independent acquisition (DIA) proteomics, milk fat globule-epidermal growth factor 8 (Mfge8) was identified as a critical factor facilitating SHTL-enhanced efferocytosis. Chip-PCR and GW9662 were applied to explore the involvement of peroxisome proliferator-activated receptor gamma (PPARγ) signaling.ResultsSHTL markedly attenuated the progression of AS, demonstrated by reduced plaque formation within both the aortic root and aorta, diminished plasma lipid concentrations, and suppressed inflammatory responses. In vitro assays using BMDMs revealed that SHTL significantly inhibited foam cell formation and inflammation induced by Ox-LDL and LPS. Furthermore, SHTL enhanced efferocytosis both in vivo and in vitro by upregulating Mfge8 expression. Treatment with GW9662 abolished these beneficial effects, confirming that SHTL exerts its protective actions via activation of the PPARγ/Mfge8 pathway.ConclusionSHTL demonstrates significant anti-inflammatory and lipid-regulatory effects, attenuating AS progression through the PPARγ/Mfge8 pathway, thereby enhancing macrophage efferocytosis. These findings highlight a novel mechanism by which SHTL may contribute to preventing and treating atherosclerotic diseases.